2007
DOI: 10.1007/s00213-007-0710-6
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of the novel, selective, 5-HT2C receptor agonist WAY-163909 in rodents

Abstract: Taken together, these results demonstrate that the novel 5-HT2C receptor agonist WAY-163909 produces rapid onset antidepressant-like effects in animal models and may be a novel treatment for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 38 publications
2
64
0
Order By: Relevance
“…However, either 5-HT2C-R gene knockout or systemic treatment with the selective 5-HT2C-R antagonists SB 242084 or RS 102221 has been shown to both potentiate the antidepressant-related effects of SRIs in the tail suspension test and augment the increases in cortical and hippocampal ECF serotonin levels produced by SRI treatment (Cremers et al, 2004(Cremers et al, , 2007. On the other hand, systemic treatment with the novel 5-HT2C-R agonists WAY 163909, RO 600175 also exert antidepressant-like effects in a range of rodent assays (Cryan and Lucki, 2000;Martin et al, 1998;Rosenzweig-Lipson et al, 2007). These data have not been reconciled but they imply that the influence of genetically driven variation in human HTR2C function on risk for depression in humans may be complex.…”
Section: -Ht2c Receptorsmentioning
confidence: 99%
“…However, either 5-HT2C-R gene knockout or systemic treatment with the selective 5-HT2C-R antagonists SB 242084 or RS 102221 has been shown to both potentiate the antidepressant-related effects of SRIs in the tail suspension test and augment the increases in cortical and hippocampal ECF serotonin levels produced by SRI treatment (Cremers et al, 2004(Cremers et al, , 2007. On the other hand, systemic treatment with the novel 5-HT2C-R agonists WAY 163909, RO 600175 also exert antidepressant-like effects in a range of rodent assays (Cryan and Lucki, 2000;Martin et al, 1998;Rosenzweig-Lipson et al, 2007). These data have not been reconciled but they imply that the influence of genetically driven variation in human HTR2C function on risk for depression in humans may be complex.…”
Section: -Ht2c Receptorsmentioning
confidence: 99%
“…We also examined possible between-strain differences on schedule-induced polydipsia (SIP) task that has been suggested as a model of OCD (Platt et al, 2008;Rosenzweig-Lipson et al, 2007;Woods et al, 1993;Woods-Kettelberger et al, 1996). As impulsive behaviors have been related to monoaminergic dysfuctions (Winstanley et al, 2006), we assessed basal neurochemical function in the striatum and nucleus accumbens of RHA-I and RLA-I rats.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it has received significant attention as a target for drug discovery. Several novel 5-HT 2C receptor agonists have been described, including [7bR,10aR)-1,2,3,4,8,9,10, 10a-octahydro-7bH-cyclopenta-[b] [1,4]diazepino [6,7,1hi]indole] (WAY-163909) (Dunlop et al, 2005;Marquis et al, 2007;Rosenzweig-Lipson et al, 2007), 2-[(3-chlorophenyl)methoxy]-6-(1-piperazinyl)pyrazine hydrochloride (CP-809101) (Siuciak et al, 2007), and lorcaserin (Thomsen et al, 2008), and shown to have activity in preclinical animal models used to evaluate potential antipsychotic, antidepressant, and antiobesity activity. Moreover, lorcaserin has demonstrated clinical efficacy in obesity (Smith et al, 2009).…”
Section: Introductionmentioning
confidence: 99%